2020
DOI: 10.1097/md.0000000000022975
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori infection and irritable bowel syndrome

Abstract: Background: In recent years, the incidence of IBS has gradually increased, and it is considered as one of the most common functional gastrointestinal diseases. However, the etiology of IBS is still unclear, and expectations are rising for more targeted treatments. Many clinical trials have explored the link between Helicobacter pylori ( H pylori ) and IBS, with different conclusions. Therefore, we conducted a meta-analysis to explore whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…A meta‐analysis conducted up until January 2021, which included 22 studies with a total of 206,911 patients in case–control studies, indicated that individuals infected with H. pylori had a higher likelihood of developing metabolic syndrome in both case–control studies (pooled OR = 1.19, 95% CI: 1.05–1.35) and cohort studies (pooled HR = 1.31, 95% CI: 1.13–1.51) 25 . Another more recent retrospective cross‐sectional study in China reinforced these associations within the same population, utilizing five diagnostic criteria simultaneously (IDF, ATP III, JIS, CDS, and CDS DM) 26 …”
Section: Clinical Evidence Of the Involvement Of Helicobacter Pylori ...mentioning
confidence: 90%
See 1 more Smart Citation
“…A meta‐analysis conducted up until January 2021, which included 22 studies with a total of 206,911 patients in case–control studies, indicated that individuals infected with H. pylori had a higher likelihood of developing metabolic syndrome in both case–control studies (pooled OR = 1.19, 95% CI: 1.05–1.35) and cohort studies (pooled HR = 1.31, 95% CI: 1.13–1.51) 25 . Another more recent retrospective cross‐sectional study in China reinforced these associations within the same population, utilizing five diagnostic criteria simultaneously (IDF, ATP III, JIS, CDS, and CDS DM) 26 …”
Section: Clinical Evidence Of the Involvement Of Helicobacter Pylori ...mentioning
confidence: 90%
“…Numerous studies have investigated the association between H. pylori infection and insulin resistance, but the results remain conflicting 26,50,51 . A previous meta‐analysis of 22 case–control studies involving 206,911 participants, covering the period from 1991 to January 2021, quantified a combined OR of 1.54 (95% CI: 1.19–1.98) for the association between H. pylori infection and insulin resistance 25 .…”
Section: Metabolic Pathways Alterationsmentioning
confidence: 99%
“…Regarding IBD, there are many evidences supporting a multifactorial genesis comprising a combination of genetic predisposition, immune response, and environment, most notably the bacterial gut microbes or luminal antigens [19]. Certain studies detected H. pylori infection among IBD patients, so they suggested a possible role of H. pylori in IBD group, although other studies suggested no possible role of H. pylori in IBD indicating that the role of H. pylori in IBD is still controversial [20]. The present study disclosed presence of H. pylori in 66.7% of CRC patients and 36.7% of IBD patients compared to 33.3% in the NC group, and analysis of data reflects nonsignificant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Es posible que la falta de asociación entre H. pylori y SII en los estudios anteriores se deba a la gran heterogeneidad de los estudios y tamaños de muestra pequeñas 24,25 .…”
Section: Evidencias En Contra De La Asociación Entre H Pylori Y Síndr...unclassified